The Importance of Ventral Hippocampal Dopamine and Norepinephrine in Recognition Memory - Titulaer, Joep; Björkholm, Carl; Feltmann, Kristin; Malmlöf, Torun; Mishra, Devesh; Bengtsson Gonzales, Carolina; Schilström, Björn; Konradsson-Geuken, Åsa (Frontiers in Behavioral Neuroscience, 2021)
Dopaminergic neurons originating from the ventral tegmental area (VTA) and the locus coeruleus are innervating the ventral hippocampus and are thought to play an important role for efficient cognitive function. Moreover, these VTA projections are hypothesized to be part of a functional loop, in which dopamine regulates memory storage. It is hypothesized that when a novel stimulus is encountered and recognized as novel, increased dopamine activity in the hippocampus induces long-term potentiation and long-term storage of memories. We here demonstrate the importance of increased release of dopamine and norepinephrine in the rat ventral hippocampus on recognition memory, using microdialysis combined to a modified novel object recognition (NOR) test. We found that presenting rats to a novel object significantly increased dopamine and norepinephrine output in the ventral hippocampus. Two hours after introducing the first object, a second object (either novel or familiar) was placed in the same position as the first object. Presenting the animals to a second novel object significantly increased dopamine and norepinephrine release in the ventral hippocampus, compared to a familiar object. In conclusion, this study suggests that dopamine and norepinephrine output in the ventral hippocampus has a crucial role in recognition memory and signals novelty.